MIKROENKAPSULASI PIGMEN DARI KUBIS MERAH: STUDI INTENSITAS WARNA DAN AKTIVITAS ANTIOKSIDAN - Diah Mustika Lukitasari; Renny Indrawati; Rosita Dwi Chandra; _ Heriyanto; Leenawaty Limantara (Jurnal Teknologi dan Industri Pangan, 2017)
Utilization of artificial food colorants has obtained particular concern for long time consumption. Red cabbage (Brassica oleracea L. var. capitata forma rubra L.) was extracted to produce a candidate for natural food colorant through a one-step physical extraction and microencapsulation. The color strength was determined by measuring: (1) tinctorial strength, (2) color degradation kinetics at various pH, and (3) thermostability. Yield level and antioxidant activity were enclosed as supporting data. The results showed that extract of red cabbage exhibited vivid red until green color at various pH and was nearly stable at pH 2 and 3, meanwhile its thermostability was fairly good at pH 3, 4, 8, and 9. The encapsulated red cabbage extract produced high color intensity at pH 2 for red color and pH 9 for blue color with a yield level of  5.53%. It also showed antioxidant activity with IC50 value of 725.65±0.086 ppm in methanol solvent and 258.25±0.097 ppm in water-methanol solvent.